Characterizing amorphous silicates in extraterrestrial materials: Polymerization effects on Raman and mid‐IR spectral features of alkali and alkali earth silicate glasses. Issue 5 (21st May 2017) - Fu, Xiaohui; Wang, Alian; Krawczynski, Michael J.
Abstract: Amorphous silicates are common in extraterrestrial materials, especially in carbonaceous chondrites of petrologic types 1 and 2. In addition, high percentage of amorphous components and poorly crystalline phyllosilicates were found in the mudstones at Gale Crater by the CheMin instruments on board of Mar Curiosity rover, which illustrates the importance of characterizing amorphous silicates in future planetary surface explorations. The structure of an amorphous silicate can vary in two aspects: the degree of polymerization and the degree of crystallinity. Here we present the first phase study on characterizing synthetic alkali and alkali earth silicate glasses with different degrees of polymerization by using vibration spectroscopy. Compared with crystalline silicates, their Raman and mid‐IR spectra show broad spectral peaks but have the similar peak positions. We find that a change in the degree of polymerization of these silicate glasses affects their Raman band positions, especially the ratio of Raman band intensities, as well as the positions of the Christiansen feature and reststrahlen bands in their mid‐IR absorbance spectra. Based on these observations, we establish a calibration curve that could enable semiquantification of the polymerization degree of silicate glasses in planetary surface/subsurface materials during future robotic planetary surface exploration missions. Key Points: Silicate glasses with different degrees of polymerization are characterized by using vibration spectroscopy Raman peak intensities and positions systematically evolve with the degree of polymerization of silicate glasses A calibration curve was established to quantify the degree of polymerization of amorphous silicates